Biotic drivers of seedling establishment in Neotropical savannas: selective granivory and seedling herbivory by leaf‐cutter ants as an ecological filter. (28th September 2016) - Costa, Alan N.; Vasconcelos, Heraldo L.; Bruna, Emilio M.
Summary: Herbivory has been shown to have prominent top‐down effects on vegetation in Paleotropical savannas, where consumers of early stages of life history act as demographic bottlenecks. Such impact has been largely ignored in Neotropical savannas, however, despite insect consumption being linked to reduced recruitment of woody species. We hypothesize that Atta leaf‐cutter ants – the prevalent herbivores in the Neotropics – alter the establishment of woody plant seedlings in the Brazilian Cerrado by reducing seed availability and seedling survival. We also hypothesize that the demographic effects will be species‐specific. To test these hypotheses, we experimentally (i) compared seed removal in areas with and without Atta foraging and (ii) compared the survivorship of seedlings exposed to or protected from Atta foraging. Both experiments were performed with the same common Cerrado species which allowed us to evaluate the potential net effects of consumers at the population and community levels. Overall seed removal rates in sites with Atta foraging were greater than those where ants were absent (59.2% and 39.2% of seeds removed, respectively). There were differences in removal for 10 of the 12 tested species, with per species removal 1.1‐ to 3.8‐fold greater in areas with Atta foraging. On transplanted plants, 45% of seedlings exposed to Atta were attacked, resulting in a survival 7.6% lower than that of protected seedlings. Seedling survival was 11.8–31.5% lower in five species, with the largest differences in survival between treatments during the dry season. Taken together, these results support the hypothesis that consumers can lead to demographic bottlenecks in Neotropical savanna plant species, with effects varying among life‐history stages and between species. Synthesis . Granivory by ants has been linked to reduced seedling recruitment of woody species in the Brazilian Cerrado. Our results show that leaf‐cutter ants may largely limit early seedling establishment of woody species by reducing seed availability and seedling survival with differential species‐specific effects. Atta ants may therefore be acting as an ecological filter, which coupled with potential selectivity in foraging on reproductive life‐history stages, may ultimately influence the relative abundance of different species and hence the structure and composition of Cerrado vegetation. Abstract : Leaf‐cutter ants may largely limit early seedling establishment of woody species by reducing seed availability and seedling survival with differential species‐specific effects. Atta ants may therefore be acting as an ecological filter, which coupled with potential selectivity in foraging on reproductive life‐history stages, may influence the relative abundance of different species and hence the structure and composition of Cerrado vegetation.